2018
DOI: 10.1097/spv.0000000000000516
|View full text |Cite
|
Sign up to set email alerts
|

Does Patient Education Augment Pelvic Floor Physical Therapy Preparedness and Attendance? A Randomized Controlled Trial

Abstract: The addition of enhanced patient counseling did not improve patient preparedness or odds of attending PFPT. Adherence behaviors surrounding PFPT attendance are multifactorial and require further qualitative research to elucidate barriers to PFPT attendance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 13 publications
1
25
2
Order By: Relevance
“…The rates of PFPT attendance and completion in our series are similar to those found by Shannon et al in a 2018 retrospective review of urogynecologic patients in another Midwest academic practice setting (66 and 29%) [8] and in a subsequent 2019 randomized trial testing the impact of enhanced counseling on PFPT attendance and completion (65 and 47%) [9].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The rates of PFPT attendance and completion in our series are similar to those found by Shannon et al in a 2018 retrospective review of urogynecologic patients in another Midwest academic practice setting (66 and 29%) [8] and in a subsequent 2019 randomized trial testing the impact of enhanced counseling on PFPT attendance and completion (65 and 47%) [9].…”
Section: Discussionsupporting
confidence: 87%
“…While a multidisciplinary approach appears to promote PFPT attendance, further study is required to determine how we can positively affect adherence and completion with this important treatment approach. Rates of attendance and completion of pelvic floor physical therapy (PFPT) with and without same-day PFPT appointment at initial urogynecology consultation Table 1 Sample description stratified by pelvic floor physical therapy (PFPT) outcomes 61 (18) 38 (17) 19 (14) Divorced/separated 99 (10) 36 (11) 26 (12) 13 (9) Widowed 96 (10) 29 (9) 22 (10) 17 (12) Insurance Participants were asked about race and ethnicity separately so numbers do not sum to 100% Table 2 Factors associated with pelvic floor physical therapy (PFPT) attendance and completion Factor PFPT attendance…”
Section: Discussionmentioning
confidence: 99%
“…Since most women need approval from their spouse or mother-in-law to seek healthcare, (264), we considered the video to be important to increase knowledge and understanding about PFMT. On the other hand, a recent study from the United States showed that the addition of an informational video did not improve patient preparedness or odds of attending PFMT (265). The authors of the study concluded that adherence behaviours and PFMT attendance are multifactorial and require further qualitative research to understand this issue in more depth.…”
Section: Pelvic Floor Muscle Training In Pregnant Nepalese Women (Papmentioning
confidence: 89%
“…Adherence to PFPT is multifactorial and includes attendance at each visit, performance of home exercise program between visits and the long-term adherence to home exercise plan [24]. Despite the efficacy of physical therapy treatment for urinary incontinence, as well as the lowrisk nature of the intervention, adherence to PFPT has been reported as lower than 50% [25,26].…”
Section: Loss Of Anterior Abdominal Wall Muscular Strength With the Pmentioning
confidence: 99%